Steak the whole story - Hayward, Tim (Quadrille, 2024)
"An encyclopaedic yet accessible journey through the world of chefs, farmers, butchers and restaurants, Steak is the essential guide for enthusiasts improving their kitchen skills or diners chasing the greatest steaks around the world. With stories, recipes, traditional cooking techniques and cutting-edge new ones, you'll never again overcook a steak or wonder which cut to buy. Plus there's a guide to butchery, a cooking course (including some steak science)... and Cow Maps. Steak takes an in-depth look at the historical, cultural and social significance of our favourite cut of meat, and how we might continue to enjoy it sustainably into a long future - it's the ultimate handbook for anyone who cares about sourcing and cooking great food"--
Titelzusatz vom Umschlag
"The whole story"-- Cover
Includes index
Keywords: Cooking (Beef); Cuisine (Buf); Kochbuch